Crania patagónica - Sardi, Marina (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
In Argentina, as well as in other countries, skeletal remains of different human groups, particularly the skull, have been the traditional material evidence used during both the old Physical and the new Biological Anthropologies. However, historical studies never focus on these materialities; but rather on theoretical and methodological changes. The goal of this study is to address some key insights about the History of Anthropology based upon cranial collections and their material, intellectual and political dimensions. The study of Marcelo Bórmida about Patagonian skulls is taken as reference in order to think about the conditions of possibility of research in our country. It is finally expected to provide some thoughts about how restitutions of human remains challenge the traditional goals of our discipline.